Relevansi Konsep Belajar Ibnu Khaldun dalam Perspektif Teori Belajar Kontemporer - Muhammad Farid Asysyauqi; Zaenal Arifin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article aims to review the concept of learning from the perspective of Ibn Khaldun. Ibn Khaldun is one of the Muslim scholars who has significantly contributed to sociological theory. However, it also offers insights that must be explored to contribute to specific learning theories. The concept of learning offered by Ibn Khaldun is compared to contemporary learning theories, including behaviorism, cognitivism, humanism, and constructivism. This research used qualitative research with a literature approach and was analyzed using content analysis techniques. The results of this study indicate that Ibn Khaldun's thoughts regarding the concept of learning have relevance to contemporary learning theory. The relevance is addressed using the term riyadhah, which is relevant to behaviorism concepts, 'aql nadzari, which is relevant to cognitivism, and madaniyyun bith thab'iy, which is relevant to constructivism.